ANALISIS FAKTOR KESULITAN MEMBACA MENULIS DAN BERHITUNG SISWA KELAS 1 B MI BUSTANUL ULUM SIDOREJO - Fitriyah (AZZAHRA, 2020)
This research is descriptive research. The subjects of this study were all students 1 B MI Bustanul Ulum Sidorejo whose class was 45 students. This study aims to see what factors affect the difficulty of reading, writing and arithmetic. data tools obtained from observation, interviews and documentation. This process begins by giving students a reading test, then after the difficulty is identified, investigates and then observes the students who have difficulty reading. The results of the study as students who are already fluent and can read, write and count but there are 3 children who still have difficulty reading, writing and arithmetic. Difficulty reading, writing and arithmetic is caused by several factors, namely environmental factors of parental attention, mentoring and supervision which are very important and affect student interest and motivation as well as student environment in the learning process. Teachers' strategies for overcoming difficulties in reading, writing and arithmetic by providing attention, training, guidance by teachers and also people so that the learning process can run smoothly.